THE RELATIONSHIP BETWEEN NUMBER OF FAMILY MEMBERS AND WEIGHT GAIN IN TODDLERS IN THE WORKING AREA OF THE BATU AJI COMMUNITY HEALTH CENTER - Sri Wulandari; Junita Henriette (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background : The current state of nutrition for the Indonesian people is still not encouraging. Various nutritional problems such as malnutrition and malnutrition, lack of Vitamin A, iron deficiency anemia, disorders due to lack of iodine and excess nutrition (obesity) are still widely spread in cities and villages throughout the country. The factors that influence this situation include the level of family ability to provide food according to the needs of family members, family knowledge and behavior in selecting, processing and distributing food at the household level, the availability of clean water and basic sanitation facilities as well as the availability and accessibility of food. quality public health and nutrition services (Depkes RI, 2007). The purpose of this study was to determine the relationship between the number of family members and the weight gain of children under five in the Batu Aji Community Health Center. Method : This research is an analytical survey or research that tries to explore how and why this health phenomenon occurs. Then analyze the dynamics of the correlation between phenomena or between risk factors and effect factors, by means of a cross sectional approach or collecting data at the same time. This research was conducted in the working area of Puskesmas Batu Aji, Posyandu Tulip Lestari, Posyandu Pelangi, and Posyandu Kasih, the working area of Puskesmas Batu Aji, Batam City. The population in this study were 596 mothers who had toddlers at Tulip Lestari Posyandu, Pelangi Posyandu, and Posyandu Kasih, the working area of Puskesmas Batu Aji, Batam City. Researchers want to measure the relationship between the dependent and independent variables using the Chi Square test. The statistical test criteria used Chi Square. Result : It can be seen that the frequency of the number of family members most of the members of the extended family is 62 people (62%). that there are more respondents who have children above the red line as many as 71 people (82.6%). Chi-Square obtained a p-value of 0.542 because the p-Value> 0.05 means that Ho is accepted Conclusions :It is known that there is no relationship between the number of family members and body weight under the red line for under-five children in the working area of the Batu Aji Health Center, Batam City with a p value = 0.542